Aspectos psicossociais e condições bucais em dependentes químicos internados para desintoxicação - Ciesielski, Francisco Isaak Nícolas [UNESP] (2013)
Objective: This study assessed health of patients with chemical dependency correlating effect of these drugs with changes of normal structures of the oral cavity. Methods: 108 patients who initiated detoxification therapy were evaluated clinically and obtained data on the health, socioeconomic, on the use of licit and illicit drugs by means of a structured questionnaire and microbiological analyses. Results: Among the patients 70.3% had a significant change in the oral cavity, as most prevalent are dental (dental attrition, edentulism) and periodontal (gingivitis and periodontitis). Also mucosa alterations were seen (xerostomia, oral leukoplakia and keratosis) as well buccal microbiota alterations. One can show that drug use begins from friends with the intention of amusement or social acceptability. Among the behavioral changes highlight problems generated by the social implications of drug use and symptoms of depression. Conclusion: Infectious oral diseases and behavioral and cognitive changes are strongly associated with addiction and many of these manifestations are unifamiliar to health professionals, which often can compromise results of medical and dental treatments.